Karakteristik Kimia Kopi Arabika Bubuk dari Varietas Linie-S dan Sigararutan - Hasriani; Sitti Arwati (JURNAL AGROINDUSTRI HALAL, 2024)
One of eastern Indonesia's top places for producing high-quality coffee, particularly Arabica coffee, is Gowa Regency. Ground coffee's chemical composition is significantly influenced by the post-harvest and coffee harvesting procedures used to produce it. The Indonesian National Standard (SNI) 01-3542-2004 compares a range of values about ground coffee that can be used to evaluate the coffee's quality. This study's goals are to determine which arabica coffee varieties have chemical attributes that are in line with (SNI) 01-3542-2004 and to look into the chemical makeup of ground arabica coffee from the Gowa Regency's linie-S and sigararutan kinds. The Sigararutan and linie-S types of arabica coffee beans, both from the Tinggimoncong District, were utilized in the study. In the research investigation, a non-factorial fully randomized design (CRD) was used in three replications. Chemical analysis examines the composition of coffee extract, moisture, ash, and caffeine. The results showed that powdered arabica coffee of the Linie-S variety differed considerably from powdered arabica coffee of the Sigararutan type in terms of water content, ash content, and caffeine content. The amounts of coffee extract in the two samples, however, were not substantially different from one another. The water, ash, caffeine, and coffee essence contents of the Linie-S and Sigararutan varieties of powdered arabica coffee satisfy the requirements outlined in (SNI) 01-3542-2004 for ground coffee.